Differences in the domains of achievement motivation based on gender and developmental group - Clark, Gina L. (2010)
The following study examined differences in domains of achievement motivation based on gender and developmental group. Participants included 129 males and females. The developmental groups in this study consisted of preadolescents (9-12 years) and adolescents (18-19 years). Participants were administered a demographics form and the Achievement Motivation Profile (AMP: Friedland, Mandel, & Marcus, 1996). A 2 x 2 MANOVA was used to analyze differences in achievement motivation domains (Achiever, Motivation, Competitiveness, and Goal Orientation) based on gender and developmental group. It was hypothesized that males would score higher than females on Competitiveness, while females would score higher than males on Achiever. Additionally, it was expected that preadolescents would score higher on Motivation than adolescents, and adolescents would score higher on Goal Orientation than preadolescents. Results revealed a statistically significant difference between males and females on Achiever, Goal Orientation and Motivation. There were no interaction effects (between gender and developmental group) or main effects for developmental group observed. Implications and directions for future research will be discussed in the paper.